Characterization of an autoregulated response element in the mouse retinoic acid receptor type beta gene. - Sucov, H M (1990)
A sequence that confers transcriptional responsiveness to retinoic acid was identified in the promoter of the mouse retinoic acid receptor (RAR) beta gene. This response element consists of a direct repeat of the sequence GTTCAC, separated by five nucleotides. Direct binding of the RAR to this sequence was demonstrated by gel retardation and immunoprecipitation assays. This element conferred retinoic acid responsiveness on heterologous promoters via all three subtypes of RAR yet failed to support transcriptional activation by the thyroid hormone, estrogen, glucocorticoid, or vitamin D receptors. Surprisingly, a high level of retinoic acid-dependent activation was seen in the absence of transfected RAR in 10 of 10 vertebrate cell lines, many functionally characterized previously as lacking endogenous receptor. This demonstrates an unusually high sensitivity of the retinoic acid response element to low levels of receptor and suggests expression of RAR in a wide variety of tissue types.